Research on the Construction of Life Cycle Assessment Model for Sponge Facilities - Xie, Xiao; Han, Yongchen (International Journal of Natural Resources and Environmental Studies, 2025)
As a key green infrastructure for urban storm water management, the life cycle environmental impact assessment of sponge facilities is crucial for optimal design and sustainable decision-making. This study systematically examines the methodological steps, software tools, and their comparative advantages in conducting life cycle assessment for sponge facilities. Furthermore, a framework for establishing a life cycle assessment model tailored to sponge facilities is proposed. This research provides methodological support for the precise environmental assessment of sponge facilities and low-carbon urban planning, and promotes the sustainable development of green infrastructure.